The Effect of Health Promotion on Personal Protective Equipment on Boat Service Behavior in Handling Drowning Victims on the Solo River, Patihan Village, Widang District, Tuban Regency - Karyo Karyo; Moh. Ubaidillah Faqih (Aloha International Journal of Health Advancement (AIJHA), 2020)
The use of PPE is one of the problems in the world of crossing work. the use of personal protective equipment along with its functions and benefits, so that it is expected to change the behavior of users of water transportation services to be good and can ensure their safety. This study used a one group pre-post test design. The sampling technique was taken using Simple Random Sampling on boat services. Data collection techniques using a questionnaire sheet with the number of respondents 19 people. Data analysis using Wilcoxon test. The results showed that there was an effect of health promotion of personal protective equipment on boat service behavior in handling drowning victims on the Bengawan Solo River, Patiahan Widang Tuban Village, this was evidenced by the Wilcoxon test which obtained a value of p = 0.000 (p